Stink Bug Communication and Signal Detection in a Plant Environment - Andrej Čokl; Alenka Žunič-Kosi; Nataša Stritih-Peljhan; Maria Carolina Blassioli-Moraes; Raúl Alberto Laumann; Miguel Borges (Insects, 2021)
Plants influenced the evolution of plant-dwelling stink bugs’ systems underlying communication with chemical and substrate-borne vibratory signals. Plant volatiles provides cues that increase attractiveness or interfere with the probability of finding a mate in the field. Mechanical properties of herbaceous hosts and associated plants alter the frequency, amplitude, and temporal characteristics of stink bug species and sex-specific vibratory signals. The specificity of pheromone odor tuning has evolved through highly specific odorant receptors located within the receptor membrane. The narrow-band low-frequency characteristics of the signals produced by abdomen vibration and the frequency tuning of the highly sensitive subgenual organ vibration receptors match with filtering properties of the plants enabling optimized communication. A range of less sensitive mechanoreceptors, tuned to lower vibration frequencies, detect signals produced by other mechanisms used at less species-specific levels of communication in a plant environment. Whereas the encoding of frequency-intensity and temporal parameters of stink bug vibratory signals is relatively well investigated at low levels of processing in the ventral nerve cord, processing of this information and its integration with other modalities at higher neuronal levels still needs research attention.